HOW NON-NATIVE EARLY CHILDHOOD LEARN ENGLISH (A DESCRIPTIVE STUDY ON A GROUP OF SUNDANESE EARLY CHILDHOOD IN CIJEUNGJING SUB-DISTRICT, CIAMIS REGENCY, WEST JAVA – INDONESIA) - Dani Ardiansyah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
Learning English for non-native early childhood is not easy (Hashemi & Azizinezhad, 2011),it includes in Indonesia notably in Ciamis Regency, West Java. It needs the appropriatemethods, techniques and materials to help the non-native early childhood ease learning English.This study aims to report what appropriate method, technique, and material applied to teachEnglish to non-native Sundanese early childhood in Ciamis regency, West Java Province. Thisstudy was carried out to a group of six non-native Sundanese early childhood. Afterwards, thewriters set forth a research question: What appropriate method, technique, and material appliedto teach English to non-native Sundanese early childhood? To answer the research question,the writers employed a desriptive study as suggested by Wragg (1999) and Fraenkel, Wallen,and Hyun (2012) at which they observed the process of teaching and learning English towardsnon-native Sundanese early childhood during September 2018 - February 2019. The resultsshowed that the appropriate method applied in teaching English to non-native Sundanese earlychildhood was the Audio-Lingual Method (ALM). Meanwhile, the appropriate techniqueapplied in teaching English to non-native Sundanese early childhood was drilling. In addition,the appropriate material applied in teaching English to non-native Sundanese early childhoodwas video such as BLIPPI. To sum up, through employing the appropriate method, technique,and material, the non-native Sundanese early childhood feel enjoyed and excited in learningEnglish listening and conversation.